Neurocellular profile in the brain of the African giant rat (Cricetomys gambianus, Waterhouse, 1840) (2014)
The African Giant Rat (AGR) recently gained international prominence due to its ability to detect landmines and tuberculosis using olfactory and cognitive cues. However, a striking gap exists in the literature on the neurocellular components that govern these unique abilities. This study investigated and described the morphology of cellular components, useful morphometric parameters and neurogenesis profile of the brain of the AGR across age groups. Forty male AGR comprising 10 neonates, 15 juveniles and 15 adults obtained from the wild were used for this study. Brains were harvested, weighed and studied grossly. Cyto-architectural study on different brain regions was performed using Nissl and Haematoxylin-Eosin stains. Differential staining of sections was achieved using Golgi silver impregnation and Kluver Barrera methods for cortical neurons and myelin morphology respectively. Immunohistochemical identification of individual neurocellular populations was done using the following biomarkers: glia fibrillary acidic protein for astrocytes, 2’, 3’ cyclic nucleotide phosphodiesterase for oligodendrocytes, ionizing calcium binding adhesion molecule-1 for microglia, doublecortin for immature and migrating neurons and Ki-67 for proliferative neuronal cells. Histomorphometric analysis was carried out using the Axioskop and TSview photomicrographs. Findings were compared across age groups and quantitative data were analysed using One-way ANOVA at p = 0.01. Gross morphology showed part insertion of the falx cerebri between the olfactory bulbs (OB). Cyto-architecture revealed a persistent external granular layer in the post-neonatal cerebellum and multilayered ependymocytes in the ventricular lining. The presence of 4 to 8 glomerular cell layers and myelination across all layers were observed in the OB. Dense spiny multipolar populations of cortical neurons were found in layers II, III and V of the cerebral cortex. Astrocytes demonstrated age related changes and morphological heterogeneity with eight sub-types. Five oligodendrocyte and two microglia classes were identified. Doublecortin and Ki-67 positive cells were demonstrated in the active neurogenic sites (sub-ventricular zone (SVZ) and dentate gyrus (DG) of hippocampus). Other sites were the cortex, cerebellum, anterior commissure and olfactory bulb. Histomorphometric values in different brain regions in adults, juveniles and neonates include maximum cortex width (19.27±0.2mm, 20.67±0.2mm, and 11.75±0.6mm) and cortex volume (2.84±0.0cm3, 3.16±0.1cm3 and 0.23±0.0cm3) respectively. Ki-67 cell count in the SVZ and DG respectively were also highest in juveniles (45530±13950 and 12480±7860) as against adults (6880±340 and 1130±150) and neonates (21145±8395 and 11800±1230). Findings in the olfactory bulb, multipolar neurons and the rare occurrence of myelination across all olfactory bulb layers indicated enhanced olfactory acumen. Increased receptive fields and synaptic glomerular surface area is also indicative of greater integrative computational capabilities. The juvenile African giant rat is clearly shown to have a greater capacity for neuroplasticity and thus, proposed as a model for rodent studies on olfaction and cognition.